2008
DOI: 10.1063/1.2970042
|View full text |Cite
|
Sign up to set email alerts
|

Wigner oscillators, twisted Hopf algebras, and second quantization

Abstract: By correctly identifying the role of central extension in the centrally extended Heisenberg algebra h, we show that it is indeed possible to construct a Hopf algebraic structure on the corresponding enveloping algebra U (h) and eventually deform it through Drinfeld twist. This Hopf algebraic structure and its deformed version U F (h) are shown to be induced from a more "fundamental" Hopf algebra obtained from the Schrödinger field/oscillator algebra and its deformed version, provided that the fields/oscillator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The situation is thus different from the case of the undeformed brackets where x F i , unlike p i , fails to transform as a vector [1]. The next important point is to check whether the operators which are rotationally invariant in the undeformed case, keep the rotational invariant property even in the deformed case or otherwise acquire an anomalous term which disappears in the limit ρ → 0.…”
Section: Twisted Rotationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The situation is thus different from the case of the undeformed brackets where x F i , unlike p i , fails to transform as a vector [1]. The next important point is to check whether the operators which are rotationally invariant in the undeformed case, keep the rotational invariant property even in the deformed case or otherwise acquire an anomalous term which disappears in the limit ρ → 0.…”
Section: Twisted Rotationsmentioning
confidence: 99%
“…In a previous work [1] it was shown that the Wigner's Quantization [2], unlike the ordinary quantization based on creation and annihilation operators acting on a Fock vacuum, is compatible with a Hopf algebra structure of its Universal Enveloping (graded)-Lie algebra; it can therefore be regarded as the natural framework to investigate Hopf-algebra preserving, twist-deformations of quantum mechanical systems * . Due to the fact that the ordinary quantization is recovered for a special choice of the Wigner's vacuum energy it is quite important to understand whether and under which prescription a Hopf algebra structure can be implemented for the ordinary quantization (creation and annihilation operators) as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we shall review the twist deformation of the fermionic Heisenberg algebra presented in [1]. The Grassmann algebra is generated by anticommuting coordinates θ α .…”
Section: The Twist Deformation Of the Fermionic Heisenberg Algebramentioning
confidence: 99%
“…In this paper we investigate the abelian twist-deformation of the fermionic Heisenberg algebra, introduced in [1], in application to the deformation of the Supersymmetric Quantum Mechanics. We remark that the abelian twist Returning to Supersymmetric Quantum Mechanics, in the second framework (generators realized as operators in a Universal Enveloping Superalgebra), besides the supercharges, the fermionic derivative operators can be constructed (and deformed).…”
Section: Introductionmentioning
confidence: 99%